Collective Performative Reading - m/ Peripeti Redaktion, For More Than One Voice (Peripeti, 2020)
For More Than One Voice (2016–) is a collective reading that investigates how we might speak and listen in more than one voice by means of resonance, polyphony, dissonance, ambiguity, plurality, and embrace. The collective reading is centred around the politics and poetics of the multiplicity of voices in performance and text, where the complexities of voice as representation are investigated.